Literary Warrant dan User Warrant untuk Merancang Konstruksi Prototipe Tesaurus - Fatmawati, Endang (Pustabiblia: Journal of Library and Information Science, 2023)
A thesaurus limits its scope to specific subjects or related to certain subjects and is a means of standardizing terms created as a tool in the process of organizing information. A principle-compliant index language is required when organizing information. A user warrant and literary warrant approach can be used to construct a thesaurus with a particular subject. User warrant means the collection of terms based on users’ frequency of use of a term, while the literary warrant is carried out with an accurate survey of a word, phrase, or term contained in literature. The results of the analysis in the form of a thesaurus prototype can be used as a tool for document indexing and information retrieval. This becomes a tool for classifying and finding collections in the library as collections with various subjects grow. A thesaurus is a form of means of supervising controlled terms post-adjustment or post-coordination. In constructing the thesaurus, an arrangement of entries is formed to show equivalence relationships, hierarchical and associative. The results of the subject thesaurus construction can be used as a basis for further thesaurus development, which is more complete for the indexing process.